REKOMENDASI LABORATORIUM LINGKUNGAN - Anwar Hadi (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2007)
Environmental laboratory is the laboratory that has the capability and authority to analyze environmental samples especially chemistry/physic/biology to support environmental management according to environmental laws. Based on the definition, environmental laboratory must be accredited according to ISO/IEC 17025 to generate accurate, continuous, and reliable environmental quality data which are defensible in terms of environmental regulations and scientific knowledge. However, compliance with regulatory and safety requirements on the operation of laboratory including laboratory waste management, environmental sampling, and quality control and assurance (QC/QA) for environmental laboratory are not covered by the International Standard. So, environmental laboratory must comply with the supplement requirement of Bapedal Decree No. 113: 2000 regarding to general guidance and technical for environmental laboratory. Until middle of 2007, PUSARPEDAL – KLH recommended 24 environmental laboratories and 8 laboratories still in progress for technically assessment.